Reciprocity in the Workplace. - Barr, A; Serneels, P (2008)
Using combined experimental and survey data, this paper provides empirical evidence that firm productivity is related to worker’s pro-social behavior in the workplace. At the firm level, we find a strong positive relationship between firm productivity and reciprocating behavior among workers. Investigating workers’ individual behavior we find a similar, strong relationship when regressing earnings, a proxy for productivity, on reciprocity. To address simultaneity we use an instrumental variable approach and find that the initial estimate was upwards biased, presumably because it did not take into account the positive feedback from earnings to reciprocity. The new coefficient remains substantially above zero, but it is statistically insignificant.